ROOM-TEMPERATURE MULTI-FERROCITY IN OFF-STOICHIOMETRIC Bi1.1FeO3 CERAMICS PREPARED BY MELT-PHASE SINTERING - Awan, M. S.; Bhatti, A. S. (The Nucleus, 2020)
Off-stoichiometric multiferroic (Bi1.1FeO3) ceramics were synthesized by the conventional powder metallurgy route by adopting the melt-phase sintering followed by rapid thermal quenching technique. Samples were sintered at four different temperatures (775-850) o C/120min in air. It was observed that high temperature sintering is desirable in order to avoid the impurity phases. Perovskite and impurity phases were identified by X-ray diffraction (XRD) analysis performed at room temperature. Ferroelectric properties were measured by plotting the P-E loops under an applied field of 80 KV/cm. Sample sintered at 850o C showed spontaneous polarization, remnant polarization, and coercive field of 14.44 ÂµC/cm2 , 5.47 ÂµC/cm2 and 25.50 kV/cm, respectively. The linear behavior of magnetization as a function of applied magnetic field confirms the antiferromagnetic nature of the BiFeO3 compound at room temperature. Scanning electron microscopic (SEM) studies revealed the dense and submicron features of the sintered samples. It is suggested that causes leading to the higher leakage currents and dielectric break down can be suppressed by adopting the melt-phase sintering followed by rapid thermal quenching technique. This technique was also found effective in increasing the density of the ceramic samples. The sintering technique developed in this work is expected to be useful in synthesizing other ceramics from multivalent or volatile starting materials.